Factors Affecting Sharia Banking Literacy - Hendra, Joni; Rustianawati, Mutimmah; Rahayu, Dwi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
Islamic financial literacy is expected to be able to increase knowledge and change people's behavior in making decisions to manage finances well in order to achieve their welfare. Therefore, the factors that influence the community's level of Sharia banking literacy are individual characteristics, promotions and government factors. This study aims to determine the effect of individual characteristics, promotions and government factors on Islamic banking literacy. This research uses a quantitative method with an associative approach. The population of this research is all members of fundraisers at BMT UGT Sidogiri Paiton Probolinggo as many as 437 customers, While the customers who were selected as respondents were based on customers who happened to to visit during January-March 2020, as many as 98 respondents. The results of the F test show that the independent variables (individual characteristics, promotions and government factors) simultaneously have a significant effect on Islamic banking literacy, While the t test results show that partially individual characteristics have an effect of 20.2% on Islamic banking literacy, promotion has an effect of 36.4% on Islamic banking literacy and government factors have an effect of 34.6% on Islamic banking literacy. So that the results of hypothesis testing both simultaneously and partially prove that individual characteristics, promotions and government policies have a significant effect on Islamic banking literacy.